History of Laparoscopy Surgery: Particularities about its Introduction and Development in Cuba - Pérez Martínez, Caridad de Jesús; Universidad de Ciencias Médicas de La Habana (Pontificia Universidad Javeriana, 2016)
Minimal access surgery has been a true revolution in the field of surgery, especially in general surgery, with the apparition of laparoscopy surgery. In this article has been made a bibliographic research with one main purpose: To describe the antecedents, origins, and development of the minimal access surgery and laparoscopy surgery in Cuba and around the world. Recent publications have been consulted, and, finally, we counting with thirty bibliographic references. A relevant conclusion has appeared: The most important foundations to the development of the laparoscopy surgery were built according to the technological advances that were made in the end of 19th century and the beginning of 20th century, the application of the robotic surgery and the surgery without traces are the proof of the unlimited development of the minimal invader process. In Cuba has been produced a development according to the reported worldwide.